Pengaruh Variasi Klon Unggul dan Bahan Pemacu Akar terhadap Pertumbuhan Stek Pucuk Melaleuca cajuputi subsp. cajuputi: The Effect of Superior Clone Variations and Root Growth Promoters on the Growth of Melaleuca cajuputi subsp. cajuputi Shoot Cuttings - Soviana, Farah; Wahyudiningsih, Tri Suwarni; Kartikawati, Noor Khomsah (JURNAL HUTAN TROPIKA, 2025)
Melaleuca cajuputi subsp. cajuputi has strong potential for development in the agribusiness sector, requiring appropriate cultivation strategies such as the selection of superior clones. This study was conducted from February to June 2025 at the Forest Plant Seed Certification and Nursery Center, Kalongan Nursery, Semarang. The research focused on the nursery stage, a critical phase in producing high-quality planting materials. The objective was to identify the most optimal clone and rooting stimulant for propagation via cuttings, using a Completely Randomized Block Design (CRBD). The first factor was ten superior clones, and the second was two rooting stimulants (Rootone F and Growtone). The overall survival rate of cuttings was 77.50%, with a rooting rate of 70.42%. Clone variation had a highly significant effect on cutting height, number of leaves, and number of roots, and a significant effect on axillary shoot number and root length. Clone 1, from Maluku, showed the best vegetative growth. The type of rooting stimulant and its interaction with clone variation had no significant effect on any measured parameter.